Europe, globalization and the coming universal caliphate - Bat Yeʼor (Fairleigh Dickinson University Press ; Rowman & Littlefield Pub. Group, 2011)
Europe, Globalization, and the Coming Universal Caliphate analyzes the modern political trends and strategies that are leading to major changes in Western civilization, America included, since the OIC strategy targets America also. Learning from theEuropean experience is crucial for Americans. Moreover this evolution is inscribed in the historical movement of Islamic theology and expansionism. It is not fortuitous but it has its own theological and political structure that must be known in the Westif we wish to live in a peaceful world.